Causes of Medication Errors and Barriers of Error Reporting in point of views of Nurses: a case study - Mahnaz Mayelafshar; Mehdi Memarpour (Kerman University of Medical Sciences, 2018)
Causes of Medication Errors and Barriers of Error Reporting in point of views of Nurses: a case study   Mayelafshar Mahnaz1*, Memarpour Mehdi2   1. Ph.D. Student of Health Services Management, Department of Health Services Management, Islamic Azad University,Tehran Sciences and Research Branch, Tehran, Iran 2. Ph.D. Student of Industrial Engineering, Department of Industrial Engineering, Islamic Azad University, Tehran Sciences and Research Branch, Tehran, Iran *Correspondence: valiasr st. Rajaie Cardiovascular Medical and Research Center, Iran University of Medical Sciences, Tehran, Iran Tel: 009823923136                                                   Email: mahnazmayelafshar@yahoo.com Abstract: Background & Objectives: Medication is the most commonly used therapeutic product in health care centers.The correct administration of medication orders is an important part of the treatment and care process, which is the major part of responsibility of nurses and medical staff. The occurrence of medication errors can cause serious health problems and threaten the safety of patients. This study was done to investigate the factors associated with nurses' medication errors and their refusal to error reporting in points of views of nurses. Methods: The present study was a descriptive-analytic study that was done cross-sectionally using error reports sent to the accreditation unit of a specialty cardiac hospital in Tehran during 2012-2018. Moreover, 102 nurses selected through randomized multistage sampling method were asked to complete a questionnaire. Mann-Whitney and Kruskal-Wallis statistical tests were used for data analysis. Results: According to the nurses' point of views, the most important barriers of error reporting were respectively crowded wards (29.6%) and fear of punishment (27.7%) and causes of medication errors were respectively high fatigue due to the nurses' overworking (40.2%), high workload and shortage of nurses in comparison to the number of patients (38.2%). Conclusion: Use of an appropriate training program to estabilish the culture of paying attention to the patients' safety as well as empowering the medical staff in this regard can be effective in reducing medication errors rate.   Keywords: Medication errors, Medication safety, Reporting barriers, Specialty hospital, Educational hospital, Nurses   Citation: Mayelafshar M, Memarpour M. Causes of Medication Errors and Barriers of Error Reporting in point of views of Nurses: a case study. Journal of Health Based Research 2018; 4(3): 245-59. [In Persian]